Two new species of Liocranidae (Arachnida: Aranei) from the Caucasus and northern Iran - Zamani Alireza; Marusik Yuri M. (K M K Scientific Press Ltd., 2022)
Two new species of Liocranidae, Agroeca angirasu sp.n. (♂, Iran) and Mesiotelus caucasicus sp.n. (♂♀, Armenia, Azerbaijan, Iran) are described and illustrated based on material collected in the Caucasus and Hyrcanian region in northern Iran. The distribution records of both species are mapped.